2022
DOI: 10.1093/nar/gkac463
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-mediated protein-tagging signal amplification systems for efficient transcriptional activation and repression inSaccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae is an important model eukaryotic microorganism and widely applied in fundamental research and the production of various chemicals. Its ability to efficiently and precisely control the expression of multiple genes is valuable for metabolic engineering. The clustered regularly interspaced short palindromic repeats (CRISPR)-mediated regulation enables complex gene expression programming; however, the regulation efficiency is often limited by the efficiency of pertinent regulators. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A few transcription factors had been cloned from the yeast genome and fused to the C‐terminus of dCas12a as the new AD candidate. Here we tested HAP4 (Stebbins & Triezenberg, 2004) and MED2, which is from the tail part of the mediator (Jeronimo et al, 2016; Petrenko et al, 2016) and has been confirmed to improve transcription (Zhai et al, 2022). The commonly used activator VPR was also included as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…A few transcription factors had been cloned from the yeast genome and fused to the C‐terminus of dCas12a as the new AD candidate. Here we tested HAP4 (Stebbins & Triezenberg, 2004) and MED2, which is from the tail part of the mediator (Jeronimo et al, 2016; Petrenko et al, 2016) and has been confirmed to improve transcription (Zhai et al, 2022). The commonly used activator VPR was also included as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a synchronized gene inhibition and activation system has been developed, providing more flexible and powerful tools for the metabolic engineering of S. cerevisiae. 104…”
Section: Crispri/crispra Systems Based On Dcas9 or Dcas9 Fused With T...mentioning
confidence: 99%
“…Increasing the recruitment of transcriptional effectors in the promoter region may improve the likelihood of achieving higher levels of transcriptional inhibition or activation . In addition to the RNA scaffold-based methods mentioned above, the strategies of recruiting inhibition/activation domains through protein scaffolds have also been developed. , For example, the protein scaffold-mediated signal amplification systems, SPY and SunTag, have been constructed in S. cerevisiae . In addition, a synchronized gene inhibition and activation system has been developed, providing more flexible and powerful tools for the metabolic engineering of S. cerevisiae …”
Section: Crispr/cas9-based Systems Used For Regulation Of Gene Transc...mentioning
confidence: 99%
See 1 more Smart Citation
“…A CRISPR-mediated regulator recruiting system has been developed to amplify transcriptional activation and repression. This system has been developed by fusing protein scaffolds (SPY and Sun Tag systems) with nuclease-deficient CRISPR proteins so that several effectors are recruited for accurate and efficient multi-regulation of target gene transcription ( Zhai et al, 2022 ).…”
Section: Recent Technologies and Future Trendsmentioning
confidence: 99%